ANALISIS YURIDIS PERJANJIAN KERJA WAKTU TERTENTU BERDASARKAN UNDANG-UNDANG KETENAGAKERJAAN DAN HUKUM PERJANJIAN - Apri Amalia; Budiman Ginting; Agusmidah Agusmidah; Yefrizawati Yefrizawati (Universitas Sumatera Utara, 2017)
ABSTRACT The labor agreement clause in PKWT in the form of a clause against the period of time the work done based on the type and nature of work, as well as a period in extension and renewal. The termination of the working relationship in the clause set in article 61 of ACT No. 13 of 2003 on Labor. Clause to rights and obligations is the trade off between the workers and employers. The main thing in the rights and obligations i.e. workers are entitled to a wage and employers shall be obliged to pay the wages, worker safety and health are entitled to work and employers are obligated to give it as well employers are entitled a good production results from the work of the workers. In the legal position of workers in article 59 paragraph (7) of the ACT. No.13 of 2003 on Labor that PKWT implementation does not comply with legislation then turn into PKWTT and affirmed in Kepmenaker No. 100/MEN/VI/2004 in article 15. As for the protection of workers, namely the protection of the right to healthcare, protection of right to health care, protection of rights of security/safety and the right end of the working relationship in the form of severance money, money reimbursement rights and money Awards working period. Keywords: worker/labour, working time agreements, employment law, the law of treaties.